2005
DOI: 10.1074/jbc.m500964200
|View full text |Cite
|
Sign up to set email alerts
|

A Phosphoethanolamine Transferase Specific for the Outer 3-Deoxy-D-manno-octulosonic Acid Residue of Escherichia coli Lipopolysaccharide

Abstract: Stoichiometric amounts of diacylglycerol were generated during the EptB-catalyzed transfer of pEtN to Kdo 2 -lipid A. EptB is an inner membrane protein of 574 amino acid residues with five predicted trans-membrane segments within its N-terminal region. An in-frame replacement of eptB with a kanamycin resistance cassette rendered E. coli WBB06 (but not wild-type W3110) hypersensitive to CaCl 2 at 5 mM or higher. Ca 2؉ hypersensitivity was suppressed by excess Mg 2؉ in the medium or by restoring the LPS core of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
144
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(150 citation statements)
references
References 52 publications
6
144
0
Order By: Relevance
“…6. PmrC is proven to be responsible for the addition of PEtN to the lipid A at the 1-phosphate residue (Lee et al, 2004;Reynolds et al, 2005). Our results have shown that none of the predicted PmrC homologues (Ybip/YhbX/YijP/Ecf3) was involved in the formation of the remaining 1-O-P-PEtN lipid A species.…”
Section: Possible Role Of the Petn Moiety In Lipid A-lipid A Moleculamentioning
confidence: 73%
See 3 more Smart Citations
“…6. PmrC is proven to be responsible for the addition of PEtN to the lipid A at the 1-phosphate residue (Lee et al, 2004;Reynolds et al, 2005). Our results have shown that none of the predicted PmrC homologues (Ybip/YhbX/YijP/Ecf3) was involved in the formation of the remaining 1-O-P-PEtN lipid A species.…”
Section: Possible Role Of the Petn Moiety In Lipid A-lipid A Moleculamentioning
confidence: 73%
“…Nevertheless, the lipid A profiles clearly indicate expression of PmrC activity, and all other homologues were governed by the same transcriptional and translational start signals. We did not include yhjW (Table 2) because YhjW (EptB) was recently reported to be responsible for the addition of PEtN to the second Kdo residue, but not to lipid A (Reynolds et al, 2005). Interestingly, YijP (CptA) in S. Typhimurium mediates the addition of PEtN to the phosphorylated heptose-I residue (Tamayo et al, 2005).…”
Section: -O-p-petn Lipid a In Mc1061mentioning
confidence: 99%
See 2 more Smart Citations
“…However, overproduction of dgkA did not affect the DAG expression, suggesting the occurrence of tight regulation as to DAG expression (17). Several genes are known to be involved in DAG biosynthesis, i.e., mdoB (22,23), pgpB (24)(25)(26), and eptB (27). The products of these genes produce DAG as committed reactions.…”
Section: Spontaneous Insertion and Diacylglycerol (Dag)mentioning
confidence: 99%